2005
DOI: 10.1007/s00787-005-0416-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural characteristics and autistic features in individuals with Cohen Syndrome

Abstract: Diagnostic criteria for Cohen Syndrome are based largely on physical characteristics, and systematic information about behaviour and social functioning is limited. Typically, individuals with this condition are described as being very sociable and as showing low rates of pathology. However, recent studies have indicated that behavioural difficulties may occur more frequently than previously suggested and that autistic features may be relatively common. The present investigation of 45 individuals with Cohen Syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Howlin et al [2005] reported a prevalence of 72% for ASD, according to the ADOS‐G and ADI‐R scales. It should be stressed, however, that diagnoses of the syndrome had been based on clinical criteria and had not been genetically confirmed.…”
Section: Main Syndromesmentioning
confidence: 99%
“…Howlin et al [2005] reported a prevalence of 72% for ASD, according to the ADOS‐G and ADI‐R scales. It should be stressed, however, that diagnoses of the syndrome had been based on clinical criteria and had not been genetically confirmed.…”
Section: Main Syndromesmentioning
confidence: 99%
“…Since then, there has been no further deterioration in her development 3 . In a recent study 8 of patients with Cohen syndrome, 57% of the sample was reported to have behavioral problems. Our patient, however, was aware of the stains on her teeth and cooperated during treatment, which resulted in a positive interaction between herself and the dentist.…”
Section: Discussionmentioning
confidence: 97%
“…Other abnormalities may include obesity, muscle hypotonia and weakness, mental disability, strabismus, narrow hands and feet with mild shortening of metacarpals and metatarsals, lumbar lordosis, and delayed puberty 5,6 . Since Cohen syndrome was first described, nearly 100 cases have been reported, 7 and its prevalence has been estimated at 1:105,000 live births 8 …”
Section: Introductionmentioning
confidence: 99%
“…Other signs and symptoms include short stature and scoliosis [12, 20]. In addition, individuals with CS have high rates of ASD or autistic features [21]. The estimated prevalence of CS is 1:105,000 [22], however, its frequency may be considerably higher due to the fact that patients are often not diagnosed until they reach their teenage or adult years.…”
Section: Case Presentationmentioning
confidence: 99%